2020
DOI: 10.1002/bdr2.1776
|View full text |Cite
|
Sign up to set email alerts
|

The detrimental effect of microplastics on critical periods of development in the neuroendocrine system

Abstract: As a result of human socioeconomic activity, industrial wastes have increased alarmingly. Plastic pollution is globally distributed across the world due to its properties of buoyancy and durability. Two broad classes of plastic-related chemicals are of critical concern for human health-bisphenol-A or BPA, and additives used in the synthesis of plastics, which are known as phthalates. Our exposure to them is ubiquitous because they are used in the production of materials that we use daily such as polycarbonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…Statements related to the recognition, attitude and behaviour of zero waste were developed by reviewing the literature [ 5 , 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and searching social networking sites (SNS), the internet [ 8 , 9 , 19 ], and newspaper articles. The suitability of statements was verified by three professionals and five zero-waste executors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statements related to the recognition, attitude and behaviour of zero waste were developed by reviewing the literature [ 5 , 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and searching social networking sites (SNS), the internet [ 8 , 9 , 19 ], and newspaper articles. The suitability of statements was verified by three professionals and five zero-waste executors.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, microplastics were detected in table salt [ 13 ], drinking water [ 14 ], and air [ 15 ], indicating that human exposure to microplastics is inevitable. Recent studies have reported the association of microplastics with the development of various diseases, including cancer [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once in the body via water or air, nanoplastics can translocate into internal organs such as lungs, liver, and fetus, causing oxidative stress and genotoxic damage . On land, nanoplastics can be taken up by plant roots and soil microbiota and pose ecological risks such as reduced shoot length in plants and decreases in microbial diversity and enzyme activities in soil. Microplastics could also alter nitrification and denitrification rates by altering microbial community in soil, similar to how it is observed in activated sludge processes. , Contaminants adsorbed on microplastics could make wastewater-derived microplastics more toxic, , and thus, can negatively affect the behavior, reproduction, and development of marine organisms such as oysters, shrimps, and copepods. For instance, microplastics adsorb heavy metals, including cadmium, copper, and zinc. Nanoplastics containing antibiotic resistance gene can translocate into the cell and increase risk by horizontal gene transfer . As microplastics from WWTPs may contain a high concentration of known carcinogens such as polyaromatic hydrocarbons, polybrominated diphenyl ethers, and polychlorinated biphenyls, , they may serve as a vector for increased cancer risk.…”
Section: Implications and Needs For Future Researchmentioning
confidence: 95%
“…Accumulation of MPs and NPs have been widely recorded in various aquatic ( Lusher et al, 2013 ; Avio et al, 2015 ; Frydkjær et al, 2017 ; Gambardella et al, 2017 ; Critchell and Hoogenboom, 2018 ; Lo and Chan, 2018 ; Naidoo and Glassom, 2019 ; Masiá et al, 2021 ; Stienbarger et al, 2021 ; Liu et al, 2022a ) (reviewed in: ( Akdogan and Guven, 2019 ; Wang et al, 2019a ; Franzellitti et al, 2019 )) and terrestrial animals ( Huerta Lwanga et al, 2017 ; Maaß et al, 2017 ; Souza Machado et al, 2018 ; Panebianco et al, 2019 ; Lu et al, 2020 ; Mackenzie and Vladimirova, 2021 ). These studies have reported significant detrimental effects on animal development and health, including intestinal defects, decreased body size, decreased survival rate and reproduction, decreased motility, altered behavior, neurotoxicity, increased inflammation, oxidative stress, genotoxicity, altered fat and energy metabolism, and changes in the microbiome ( Tosetto et al, 2016a ; Lu et al, 2016 ; Lei et al, 2018a ; Jin et al, 2018 ; Fackelmann and Sommer, 2019 ; Poma et al, 2019 ; Qiao et al, 2019 ; Li et al, 2020a ; Araújo and Malafaia, 2020 ; Crump et al, 2020 ; Hirt and Body-Malapel, 2020 ; Prüst et al, 2020 ; Solleiro-Villavicencio et al, 2020 ; Yong et al, 2020 ; Li et al, 2021a ; Lear et al, 2021 ; Tagorti and Kaya, 2022 ). MPs and NPs also pose health risks for humans.…”
Section: Microplastics and Nanoplastics Pose Health Risks For Animals...mentioning
confidence: 99%